Nexus between Basketball Players’ Advertisement and Psychological Attraction of Food Brands: A Study of Consumer Behavior towards Food Product - Yanlan Chen; Mengyuan Kong; Tsung-Hsien Kuo; Misbah ul Islam; Kuo, Yen-Ku; Showkat Ahmad Lone (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
It is vital for technology to advance and for the brand to obtain public recognition to achieve competitive supremacy. It is impossible to deploy without an adequate marketing, awareness, and execution strategy, as well as structured advertising approaches. As a result, advertising is an important strategy for marketing products to consumers. This research article makes a case for examining the psychological appeal of food brands associated with basketball players and customer behavior while making product purchases. If a well-known celebrity appears in a commercial, people will strongly influence the brand or product. Psychological Attraction (PA) and Food Brand Advertisement (FBA) were independent variables in the research framework. Customer Behavior (CB) was used as the Independent Variable. Nonetheless, data was gathered from 100 customers. SEM PLS 3 was used to analyze the collected data. The results suggested that the association between PA à CB is a non-significant link; however, the relationship between FBA àCB is significant.